P110 The role of environmental fungus in CF aspergillosis. (December 2018) - Collier, LJ; Bright-Thomas, RJ; Richardson, MD; Jones, AM
Abstract : Introduction and objectives: Aspergillus fumigatus is ubiquitous, and the most common disease causing fungus in cystic fibrosis (CF) patients. We undertook environmental sampling of our CF Centre and patient home environments to determine if environmental fungal burden reflected patient disease. Methods: An SAS microbial air sampler was used to sample 1 m 3 air in both CF inpatient and outpatient (OPD) locations. We have previously published data demonstrating that ventilation in our CF unit is below national requirements (Dennis et al . 2017). The use of high efficiency particulate air (HEPA) filtration was investigated to assess if it was a viable addition to current ventilation. Air sampling was performed at the beginning of the day, 1 hour post HEPA switch-on, and end of the day, comparing to rooms without HEPA filters. Additionally, patients were consented to home environmental sampling, with samples taken from their kitchen, bedroom, and bathroom. All samples were collected on malt agar plates and incubated at 30° for 4 days. Results: Fungal ingress was persistently demonstrated in all areas of the ward and OPD with Aspergillus fumigatus being the predominant organism in both. Ward count 0–59 colony forming units (CFU) with the exception of a positive pressure anteroom with >10 air changes/hour, which yielded negligible fungal growth 0–2 CFU. The OPD demonstrated fungal ingress in all areas 0–9 CFU, which reflected the outdoor counts whether windows were opened or closed. HEPA filtration did not reliably reduce fungal burden throughout the day. Patient homes have thus far grown relatively low counts of Aspergillus, with the exception of one patient whose home was undergoing extensive building work. No relationship was found between CFU counts in the CF centre and patient homes. Conclusions: Effective ventilation is important in limiting indoor fungal ingress; however HEPA filtration does not appear to be effective in reliably reducing environmental fungal load. Initial data did not identify a link between home environmental fungal burden and phenotype or severity of Aspergillus disease in CF. Reference: Dennis, et al . Thorax 2017;72 :P245, A216.